INTERCULTURAL COMMUNICATION – A NEW UNIVERSAL SOCIETY OF CULTURE. - Fetisova Kristina Ruzimatovna; Muratova Dilorom Mahmudovna (TADQIQOTLAR, 2025)
Abstract. The article will describe the topic “Language and intercultural communication”. The purpose of this article is to consider the relationship between language and intercultural communication, their influence on each other, as well as a discussion of possible difficulties.